On the Copper-Promoted Backbone Arylation of Histidine-Containing Peptides Using Triarylbismuthines - Chan, Hwai-Chien; Gagnon, Alexandre (Synthesis, 2022)
We report herein our detailed investigation on the histidine-directed backbone arylation of histidine-containing peptides using triarylbismuth reagents. The reaction proceeds on the backbone NH of the amino acid that precedes the histidine, the so-called n–1 position. The protocol is applicable to dipeptides where the histidine is located at the C-terminus and to tripeptides where the histidine occupies the central position. The transformation is promoted by copper(II) acetate in the presence of phenanthroline (Phen) and diisopropylethylamine in dichloromethane at 50 °C under oxygen. An excellent scope was observed for the triarylbismuthines. In all cases, the imidazole ring of the histidine is protected with a trityl group to prevent the arylation of the side chain. An ATCUN-like model is proposed to explain the observed results.
Keywords: triarylbismuthines; histidine; peptides; backbone arylation; copper catalysis